If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -2.1 = 62.5 Reorder the terms: -2.1 + 5x = 62.5 Solving -2.1 + 5x = 62.5 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2.1' to each side of the equation. -2.1 + 2.1 + 5x = 62.5 + 2.1 Combine like terms: -2.1 + 2.1 = 0.0 0.0 + 5x = 62.5 + 2.1 5x = 62.5 + 2.1 Combine like terms: 62.5 + 2.1 = 64.6 5x = 64.6 Divide each side by '5'. x = 12.92 Simplifying x = 12.92
| (2y+2y)+(4x+4x)=30 | | 2(4y-3)=3(y+5) | | 2x+57=33findx | | u+3.14=70 | | 2x+57=33 | | (x+2i)(x-2i)(x+4)=0 | | 6=J-5 | | 3y+7=2x-5 | | N/10-20=20 | | 100x-40y=320 | | 6x7/8= | | 3z+5z=0.6 | | (n)(n)+72=-17n | | 3x-5=6+x | | 6x+7=3(2x+4) | | (k)(k)-11k+30=0 | | (12y)(12y)+40y=7 | | 3x^2-8+5x=0 | | 3x+6=507 | | 10/3x1/2 | | 6d+4=-32 | | 5/6z=5/7 | | 18/sin40 | | a=bd | | p^2-14p=51 | | (d)(d)=5d | | 10c/2-32/4=56/8 | | (w)(w)=12 | | 3/7x1/7 | | 6-9(1-7n)=-21 | | -4x-16y=-12 | | 2y=-5x-3 |